Human papillomavirus (HPV) vaccination and factors related to intention to obtain the vaccine among young college women in Thailand - Nop T. Ratanasiripong; Sirinat Sri-Umporn; Duangrat Kathalae; Suda Hanklang; Paul Ratanasiripong (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Most cervical cancers are caused by genital human papillomavirus (HPV). However, it can be prevented if females receive an HPV vaccine. Nevertheless, there is limited evidence of HPV vaccination and predictors of intention to obtain the vaccine among young women in Thailand. The paper aims to discuss this issue. Design/methodology/approach - This cross-sectional study examined HPV vaccination and factors influencing intention to vaccinate among a convenient sample of college women in Thailand. The data collection was conducted via a self-administered "HPV and HPV vaccine-related knowledge, attitudes, and behaviors" questionnaire. Findings - Out of 1,030 participants, 309 (30.0 percent) were aware of HPV and the HPV vaccine. Out of these, 257 participants reported that they had not obtained the vaccine and 18 participants were unsure if they had already obtained the vaccine or not. Only 34 participants confirmed that they had received the vaccine. Among those who were aware of HPV and the HPV vaccine, 56.4 percent of them did not know that most HPV-infected persons do not show any signs or symptoms, and 53.3 percent thought that the vaccine provided protection against other sexually transmitted infections as well. Most had positive attitudes toward vaccination and subjective norms. Among the participants who had not received the vaccine, the intention to obtain the vaccine was predicted by age, knowledge, attitudes toward vaccination, and subjective norms. The reasons for not being vaccinated included the cost of the vaccine, lack of knowledge, and perception of themselves being at low risk. Originality/value - This study found low HPV vaccination among college women. However, those who had not received the vaccine intended to obtain the vaccine at some point in the future. An HPV vaccination campaign may be well tailored in order to increase the intention to obtain the vaccine which, in turn, may increase the HPV vaccination. Vaccination cost sharing should be discussed among Thai policy makers in order to alleviate the financial burden for women.